2006
DOI: 10.1007/s00264-006-0154-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of giant cell tumour of long bone with anhydrous alcohol adjuvant

Abstract: This study was designed to evaluate the feasibility and effectiveness of the use of anhydrous alcohol as an adjuvant treatment for giant cell tumours (GCTs) of long bone. Between October 1989 and January 2004, 42 GCT patients were treated and followed up for an average of 4.1 years (range 1-13 years). Mean patient age was 34 years (range 17-67 years). After curettage and additional burring, anhydrous alcohol was used as an adjuvant therapy in all patients before the bone defect was filled with bone graft or ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…If important anatomic structures, such as neurovascular bundles, come into contact with the leaked phenol, serious complications can occur. However, Oh et al [33] and Jones et al [23], in their respective series of 42 and 37 GCTs, noted no ethanol-related complications. In our study, 13 patients in the ethanol group had a Grade III tumor that was uncontained after tumor removal.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…If important anatomic structures, such as neurovascular bundles, come into contact with the leaked phenol, serious complications can occur. However, Oh et al [33] and Jones et al [23], in their respective series of 42 and 37 GCTs, noted no ethanol-related complications. In our study, 13 patients in the ethanol group had a Grade III tumor that was uncontained after tumor removal.…”
Section: Discussionmentioning
confidence: 95%
“…Two case series described the use of ethanol as local adjuvant therapy in the treatment of GCT of bone. Oh et al [33] reported a recurrence rate of 9.5% (four of 42). Jones et al [23] treated 25 primary and 12 recurrent GCTs with curettage and high-concentration ethanol, with five and three recurrences, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A high rate of local recurrence is observed after local treatment by intralesional curettage and/or cauterisation with phenol [2,[8][9][10][11]. Moreover, this treatment cannot be used satisfactorily in larger lesions with eggshell thin cortices or late presentations in which the tumour has spread to adjacent soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate was reported to be 10%, and there were no ethanolrelated complications. 27 Adjuvant therapy comprising ethanol alone, however, might be less effective because the ethanol may be diluted by blood from the bone marrow. Ethanol also has been used to rinse out the phenol during treatment of GCT of the bone because phenol is highly soluble in ethanol.…”
Section: Discussionmentioning
confidence: 99%